Irrigation efficiency for grain and dry matter yields of maize crop - Bergonci, João Ito; Bergamaschi, Homero; Santos, Antonio Odair; França, Solange; Radin, Bernadete (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this work was to evaluate the efficiency of irrigation, as well as the effect of water deficits, upon the grain yield and on the aerial biomass production by a maize crop. A field experiment was carried out at the Universidade Federal do Rio Grande do Sul, in Eldorado do Sul, Brazil, during four crop seasons, from 1993/94 to 1996/97. Using a line source sprinkler design, the crop was submitted to five levels of irrigation, ranging from field capacity to rainfed conditions. Increasing grain yields were observed as the water supply increased up to 80% of the level necessary for field capacity; the highest efficiency of irrigation was promoted between 60 and 80% levels and it was obtained when the water deficit occurred during the critical period of the crop cycle, reaching 40 kg ha-1 mm-1. By contrast, maximum values of efficiency of irrigation for aerial biomass occurred when the plants were submitted to long periods of water deficits, during the exponential crop growth. Decreasing grain yields due to water deficit were related to reductions on the number of kernels per ear and on the number of kernels per square meter, since the weight per kernel was not affected.
Keywords: Zea mays; soil water deficit; yield components